HBR's 10 must reads 2024 : the definitive management ideas of the year from Harvard Business Review. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2024)
"We've combed through the ideas, insights, and best practices from the past year of Harvard Business Review to help you get up to speed fast on the relevant concepts driving business today. Discover new ideas and sample the latest thinking from our vast array of management experts. Revisit these topics now to make sure your organization is incorporating the best, most up-to-date practices, or keep this book as a reference so that you can turn to these memorable pieces when you need them the most. The collection includes articles on leadership, diversity, and strategy, as well as articles that will help you manage yourself and others"--
Managers Can't Do It All / by Diane Gherson and Lynda Gratton -- What Is Web3? / by Thomas Stackpole -- Selling on TikTok and Taobao / by Thomas S. Robertson -- Managing in the Age of Outrage / by Karthik Ramanna -- The Five Stages of DEI Maturity / by Ella F. Washington -- The Essential Link Between ESG Targets & Financial Performance / by Mark R. Kramer and Marc W. Pfitzer -- Make the Most of Your One-on-One Meetings / by Steven G. Rogelberg -- Harnessing the Power of Age Diversity / by Megan W. Gerhardt, Josephine Nachemson-Ekwall, and Brandon Fogel -- The C-Suite Skills That Matter Most / by Raffaella Sadun, Joseph Fuller, Stephen Hansen, and PJ Neal -- Your Company Needs a Space Strategy, Now / by Matthew Weinzierl, Prithwiraj (Raj) Choudhury, Tarun Khanna, Alan MacCormack, and Brendan Rosseau -- Democratizing Transformation / by Marco Iansiti and Satya Nadella.
Includes index.
Description based on online resource; title from digital title page (viewed on November 15, 2023).
WorldCat record variable field(s) change: 050
Keywords: Success in business; Industrial management; Diversity in the workplace; Succès dans les affaires; Gestion d'entreprise.; Multiculturalisme en milieu de travail; Diversity in the workplace; Industrial management; Success in business; elektronické knihy; electronic books